Investasi & ESG: Analisis Bibliomterik - Fahruri, Arief (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This paper describes research developments in the context of ESG (Environment, Social, and Good Governance) using a bibliometric analysis approach. The bibliometric analysis method measures and analyzes literature with a quantitative approach. The analysis results show that research on ESG & investment, kata “Performance”, and “Risk” has shown significant progress since 2015. “Methodological variables” and ESG “scoring” still need to be developed in future research on ESG-related topics